Microstructure and mechanical properties of NbC–Ni cermets prepared by microwave sintering - Tang Siwen; Zhang Hao; Yang Zhifu; Liu Qian; Lv Zheng; Ouyang Cong; Qiu Xinyi (High Temperature Materials and Processes, 2022)
This study shows the application of microwave sintering (MS) on preparing NbC–10Ni and NbC–12Ni cermets, as well as the effect of its microstructure, phase formation, and mechanical properties. Results indicated that NbC–Ni cermets with a fine and uniform structure can be obtained by MS in a relatively short time. And the sintering temperature greatly influenced the microstructure and mechanical properties of NbC–Ni cermets, whereas the effect of dwell time is relatively small. With the increase of the sintering temperature, the microstructure of NbC–Ni cermets experienced sintering densification and grain growth. The strength and toughness increased first and then decreased, and the hardness increased with the increase of sintering temperature. According to the comprehensive mechanical properties, the optimized sintering process is 1,390°C and the dwell time is 15 min. At this time, no new phase formed, but the diffraction peak of the Ni phase shifted. Through analysis, it is found that the improvement mechanisms for comprehensive mechanical properties of NbC–Ni cermets mainly include grain refinement, crack deflection and bridging, and energy absorption of the ductile phase of Ni.